Improving Children's Language Skills Through Story Book and Picture Based Role Playing Methods - Melisa, Melisa; Hasibuan, Rabitah Hanum (Lembaga Riset Mutiara Akbar, 2025)
This research aims to improve children's language skills through the Role-Playing method based on picture books, especially in children aged 4-5 years. The problem identified is the lack of use of interactive learning methods. As well as the use of learning media that is less interesting, so that children are bored and not motivated by their enthusiasm for learning. This study uses a type of classroom action research which includes the Juho Elliot mode consisting of planning, implementation, observation, and reflection. The steps in this study consist of three steps, namely pre-cycle, cycle I and cycle II. The results of the study show that the Role-Playing method based on picture books is effectively used in improving children's language skills. From the test in the first cycle, there were changes and improvements. In cycle II where the success of children's language skills is seen to achieve maximum results. This can be seen in the first cycle only reaching 72.08% and in the second cycle there was an increase of 89.79%. In the first cycle, it is classified as a good category with a range of 70.00-79.00%. In the second cycle, it is in the very good category with a range of 80.00-100%. So that the research assessment indicators exceed the target. These results show that children's language skills have improved through the Role-Playing method based on picture books, which in the first cycle was only 72.08% and in the second cycle it increased to 89.79%.